Assessing Work Habits and Discipline: High School Teachers in South Sumatra Province Post In-Service Teacher Professional Education Program (PPG-DALJAB) - Harapan, Edi; Marisya, Fitria; Marsinah, Marsinah; Malini, Sherly; Purwanto, Muhammad Bambang (Universitas Wiralodra, 2024)
From the results of the research, it was found that many factors affect the professional competence of a teacher. Two of the most dominant factors influencing professional competence are